Missing wages: How to test for biased estimates in wage functions? - Michael Fertig; Katja Görlitz (Economics Letters, 2013)
This paper investigates how to test for nonresponse selection bias in wage functions induced by missing income information. We suggest an “easy-to-implement” approach which requires information on interviewer IDs and the interview date rather than hard-to-get interviewer characteristics.
Keywords: 330; Item nonresponse; Wages; Selection model